Associação entre sintomas de disfunção do Trato Urinário Inferior e relato de dificuldade de aprendizagem em crianças e adolescentes - Melissa Faria Dutra (2019)
Introduction: Symptoms of lower urinary tract dysfunction (LUTD) are often found in children and adolescents in the school period, as well as complaints of learning difficulties. Several comorbidities of LUTD have been described, but few studies have investigated the association between symptoms of LUTD and learning difficulty. Objective: To analyze the association between symptoms of LUTD and learning difficulty, considering gender and socioeconomic characteristics. Method: A cross-sectional study of a sample of 316 students. The following questionnaires were used to collect data: Dysfunctional Voiding Scoring System (DVSS), Bristol Scale, Word Reading Competency Test and Pseudowords and a questionnaire, elaborated by the researchers, for socioeconomic and sociodemographic evaluation and learning difficulty reported by the participants. Results: There was no significant association between symptoms of lower urinary tract dysfunction and reports of learning difficulties. Symptoms of LUTD were found in 49,4% of the students, being 2.68 times more frequent in females (OR = 2.68, 95% CI = 1.99-3.62). There was no significant association between symptoms of LUTD and socioeconomic and socioeconomic variables. Conclusion: Symptoms of LUTD were high among students. Being female has increased the chance of exhibiting symptoms of LUTD. No association was found between reports of learning difficulties and symptoms of LUTD. The importance of both preventive and curative approaches in school is emphasized.